1993
DOI: 10.2118/17538-pa
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of an Alkaline-Surfactant-Polymer Recovery System for the West Kiehl Field

Abstract: The West Kiehl Unit, Crook County, Wyoming produces from the Minnelusa Lower "B" Sand reservoir. Original oil in place (OOlP) is estimated at 238,481 m 3 . Estimated ultimate primary production is 27,028 m 3 or 11% OOlP. Four enhanced oil recovery methods were considered for application in this reservoir: conventional waterflood, polymer flood, an alkaline-polymer flood, and an alkalinesurfactant-polymer (ASP) flood.Estimated ultimate recoveries are 95,392 m 3 (40% OOlP), 95,392 m 3 (40% OOlP), 95,392 m 3 (40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 9 publications
1
41
0
1
Order By: Relevance
“…Alkaline-surfactant-polymer (ASP) flooding can effectively reduce oil residual saturation to reduce interfacial tension (IFT) and the mobility ratio between the water phase and oil phase (Clark et al 1988;Meyers et al 1992;Vargo et al 1999). Alkali is added in ASP flooding to decrease the quantity of the surfactant through competitive adsorption with the surfactant and reaction with petroleum acids in crude oil to generate a new surfactant (Pope 2007;Rivas et al 1997).…”
mentioning
confidence: 99%
“…Alkaline-surfactant-polymer (ASP) flooding can effectively reduce oil residual saturation to reduce interfacial tension (IFT) and the mobility ratio between the water phase and oil phase (Clark et al 1988;Meyers et al 1992;Vargo et al 1999). Alkali is added in ASP flooding to decrease the quantity of the surfactant through competitive adsorption with the surfactant and reaction with petroleum acids in crude oil to generate a new surfactant (Pope 2007;Rivas et al 1997).…”
mentioning
confidence: 99%
“…Important differences in the shape of the wetting phase capillary desaturation curve are seen when our data is compared with data from the literature 23,24,25,26 obtained using both centrifuge displacement and dynamic displacement methods for desaturating the core ( Figure 1.3). It is observed that all the centrifuge data (unfilled data points) appear to follow a slightly different trend than the dynamic displacement data (filled points).…”
Section: Resultsmentioning
confidence: 75%
“…It builds on the previous understanding developed for alkaline surfactant flooding 23,24 . Also, this technology has found many applications during the past decade when it was commonly thought that surfactant flooding was not economical because of the expense of the surfactant [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] .…”
Section: Surfactant Formulationsmentioning
confidence: 99%
“…Generally speaking, the application of chemical flooding in carbonate reservoirs is complicated by increased uncertainties. Clark et al (1993) implemented an ASP design on the West Kiehl Unit at Crook County, WY. The design was based on laboratory coreflood that recovered 23% OOIP beyond waterflood.…”
Section: Surfactant-polymer (Sp) Floodingmentioning
confidence: 99%